Long-Term Survival Outcomes of Modified-FOLFOXIRI Plus Cetuximab Versus Bevacizumab in RAS / BRAF Wild-Type Metastatic Colorectal Cancer: Final Analysis of the DEEPER Trial - Yu Sunakawa; Manabu Shiozawa; Takanori Watanabe; Hirofumi Ota; Hisateru Yasui; Taichi Yabuno; Mitsuyoshi Tei; Mitsugu Kochi; Dai Manaka; Hisatsugu Ohori; Tatsuro Yamaguchi; Tamotsu Sagawa; et al. (Journal of Clinical Oncology, 2026)
The randomized phase II DEEPER trial (jRCTs061180022) previously reported superior depth of response with modified 5-fluorouracil, leucovorin, oxaliplatin and irinotecan (m-FOLFOXIRI) plus cetuximab versus bevacizumab in patients with RAS wild-type metastatic colorectal cancer (mCRC). Here, we report updated final survival outcomes and exploratory subgroup analyses focusing on RAS / BRAF wild-type and left-sided tumors. Final overall survival (OS) and progression-free survival (PFS) were analyzed in the per-protocol set (PPS) with exploratory subgroup analyses according to the presence of liver-limited disease and sex, using extended follow-up data. There were no differences in PFS and OS in the PPS. In patients with RAS / BRAF wild-type and left-sided tumors, median PFS was longer with cetuximab than with bevacizumab (14.8 v 11.9 months; hazard ratio [HR], 0.71 [95% CI, 0.52 to 0.97]; P = .029). The median OS was 50.2 months for cetuximab and 40.2 months for bevacizumab (HR, 0.74 [95% CI, 0.53 to 1.05]). In the exploratory analyses, cetuximab-based therapy was associated with longer OS in male patients (HR, 0.59; P = .016) and in patients with extrahepatic disease (HR, 0.60; P = .014). In conclusion, the DEEPER trial suggests that m-FOLFOXIRI plus cetuximab achieves superior tumor shrinkage and may be associated with favorable outcomes in selected patients with RAS / BRAF wild-type and left-sided mCRC, with exploratory signals of benefit in male patients and those with extrahepatic disease.